(untitled) (Research, Society and Development, 2023)
All of Latin America is endowed with peculiarities in the housing context. Mainly by the metropolises, as they receive a significant number of migrants. Factors such as accelerated urbanization, industrialization lagging behind other countries, military regimes, among others. In 1960, the housing situation worsened, in that period because there were no policies to meet this demand. It requires a large capital investment and involves different actors with different interests. Its production has an impact on different levels of society: economic, social, political and legal. The housing deficit in Brazil is not a recent problem, but a problem that is difficult to solve. Many families, especially low-income ones, are unable to dedicate hours, days or even years of extra work to help with the self-construction system. The housing deficit is a common social problem and its existence leads people to live in low levels of quality of life. Even so, for some families, access to urban land and adequate housing is still out of reach. In this way, the objective that this work seeks to elucidate is, to raise a comparative analysis between the MCMV housing program that was recently adopted in Brazil, in comparison with the programs adopted in Chile, and will have as a standard the last housing program that was finalized in the country. . This study is justified for the author, for deepening his knowledge in the areas of civil construction and real estate development linked to government accounting and business accounting.